Tinjauan Yuridis Pengakuan Terhadap Anak Diluar Kawin : Studi Atas Penetapan Nomor : 89/Pdt.P/ 2015/Pn.Klaten - Ratu Agung Ayu Sasmita Dewi; Daingsa Wagian (Fakultas Hukum Universitas Mataram, 2022)
This research aims are to know judge’s legal consideration and its legal consequences on the recognition of out of marriage children according to the decree number 89/Pdt.P/2015/PN.Klaten. This research was conducted in normative legal research which applied statute and conceptual approaches. according to research’s result, it is found several things as follow, first of all, judge’s legal consideration in the form of written evidences national identification, marriage deed, birth deed and family card (2). witnesses are consist of two people, and (3). Article 49 paragraph (1) Law Number 23 of 2006 on Citizens Administration. Secondly, legal consequences of parent recognition creates rights and duties between child and parents, thus out of marriage children has civil relations with their parents.